GEOLOGICAL STRUCTURE AND COMPOSITION OF THE CURONIAN SPIT (BALTIC SEA) - Kharin G.S.; Kharin S.G. (My University, 2006)
The paper presents new data on geology of the Curonian Spit based on results of the study of data on the engineering-geological transect compiled during the construction of gas pipe in the Russian sector of the spit. The data show that, along with eolian sand, peat deposits recovered in both its Russian and Lithuanian sectors make up a significant portion of the spit (data on the Lithuanian sector are adopted from the available literature). Based on new data, existing concepts on geology, paleogeography, geoecology, and stability of the Curonian Spit are discussed and refined. © Pleiades Publishing, Inc. 2006.